The Plato papers : a novel - Ackroyd, Peter, 1949-; Vintage (London : Vintage, 2000)
Plato, London's greatest orator at the turn of the thirty-eighth century, regularly expounds upon the absurdities of life in the Age of Mouldwarp, a period that stretched from A.D. 1500 to A.D. 2300; but a journey to the Underworld yields a shocking discovery and Plato winds up on trial for introducing uncertainty to the world.
Keywords: Fiction, English; Philosophers -- Fiction; Time travel -- Fiction; Fantastic fiction; Historical fiction